Designing A Future Food, Plant Based Protein Blend to Promote Sustainable Nutrition - Raj Edwina; Himanshu Chaurasia; Sachdev Meenakshi; DM Mahesh; Akshatha Balakrishna; Rajeena Shahin (Revista Electronica de Veterinaria)
Background : Sustainable nutrition is environment friendly which promotes individuals’ health and wellbeing that has a low environmental pressure . It’s easily accessible, affordable, safe, and equitable that are culturally acceptable hence it is imperative to design recipes or blends that provides an optimal source of nutrition through plant based diets that will eventually reduce the dependency on animal source . Aim and Objectives: An attempt to formulate plant based blend to source vital nutrients like protein , iron , essential fats for those adopting to plant based diets . To design recipe that provides an optimal amount of nutrients that helps to promote sustainable diets .Materials & Methods : Ingredients to formulate plant based blend involved sprouted peas ,niger seed ,low glycaemic index potato & pumpkin seed. The total nutritive value of 120ml formula provided 106kcal ,5.5g protein, 9.5g carbohydrate , 4.4g fat and 2.1mg iron. Sprouted peas and low glycaemic index potatoes were leached , cooked and blended. Results: The end product can be used as a ready to use soups ,tube feed blend, as dosa and base for curries. The formula provides 20.7% of protein from energy with 10% of Recommended Dietary Allowance from 120ml with a potent source of iron, protein, essential fats and other micro nutrients vital while following plant based diet. The use of low glycaemic index potato which is included in less proportion of 10g in 120 ml of blend to prevent glucose spike. The overall cost of the product was 11 rupees (INR) for 120ml of blend. Conclusion: Plant based formula designed to optimize nutrient requirement as a source of vital nutrients such as protein , iron and essential fat through sustainable ingredients with an affordable cost which can be included as a tube feed blend or convert the same as pancake that can be a snack choice for those depending on plant based diet.